The Effect of Digital Service Quality on Consumer Satisfaction and Its Implications on Patient Trust at Pratama Aru Bitung Clinic - Kurnia Putri Utami; Arlette Suzy Puspa Pertiwi; Mira Veranita (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the influence of digital service quality on consumer satisfaction and its implications for patient trust at the Aru Bitung Primary Clinic, Bitung City. The research method used is a quantitative approach with an explanatory research type. Data were collected through questionnaires on 120 patients selected using purposive sampling techniques. Data analysis was carried out using Structural Equation Modeling based on Partial Least Square (PLS-SEM) with the help of SmartPLS software. The results of the study show that the quality of digital services has a positive and significant effect on consumer satisfaction, consumer satisfaction has a positive and significant effect on patient trust, and the quality of digital services also has a positive and significant effect on patient trust both directly and indirectly through satisfaction as a mediation variable. The conclusion of this study is that improving the quality of responsive, accurate, and accessible digital services is an important factor in building patient satisfaction and trust in first-tier health facilities.